(3ahGFO aj aVd GdYdje hGdJYdje hEQTGO GdeHJOis - (3HOQ GdOjf eMeO Hf EHQGgje Hf SYO Gddg Hf LeGYI GdcfGfj,J (B740 (3g` s ((3YHO dGdg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH GdYHO GdSdGe s)
(3ChdgG (B:s
(3bGd GdTjN eMeO Hf EHQGgje bGd CLhO GdChbGJ ddMaX GdCSMGQ hddHMK GdCHcQG s
(3BNQgG (B:s
(3hbO aYdg HYVge Hjf GdCSWQ GdeaQbI HGdMeQI hZjQgG hJQc Pdc Chdi eWdbkG GfJgi cdGe GHf LeGYI QMeg Gddg JYGdi JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3HBNQI aGFOI s
(3hQO ai cTa GdXfhf ai L(B1 (3U` (B386 (3Cf JPcQI GdSGeY hGdeJcde gh deDdag eMeO Hf EHQGgje Hf SYO GdOjf Hf LeGYI GdTGaYis
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs